Open Educational Resources as a Tool for Educational Equity: Evidence From an Introductory Psychology Class - Nusbaum, Amy T.; Cuttler, Carrie; Swindell, Samantha (Frontiers in Education, 2020)
A college education is becoming increasingly expensive, and the burden of this cost is often felt disproportionately by marginalized students. One aspect of rising college costs are textbook prices, which have increased at a rate that far surpasses inflation. Open educational resources (OER; free, openly-licensed course materials) are often proposed as a solution to this problem. It is not clear, however, whether these materials are equivalent in quality to standard commercial textbooks. During one semester, half of the Introductory Psychology sections at a large, public university were assigned to use OER while the other half were assigned to use the incumbent commercial textbook. Participants were asked to self-report the behaviors they engage in as a result of high textbook costs. We also examined student performance in the courses and students’ perceptions and use of the two books. We found no significant differences between textbook groups on course performance or perceptions of the book, but marginalized students (first-generation students and/or ethnic minority students) reported engaging in negative behaviors (i.e., dropping a class) more often than their peers as a result of textbook costs. These findings suggest that textbook costs disproportionately affect our most vulnerable students and the use of OER may be one solution to this problem, particularly given the equivalent performance across textbook groups.